High Capacity Aqueous Bi/BiOCl Battery in AlCl3 Electrolytes with pH Mitigation. Issue 12 (1st December 2022) - Lam, Wai-Yu Ashley; Chan, Kwong-Yu; Li, Chi-Ying Vanessa
Abstract : Rechargeable aqueous batteries have attracted much attention for large-scale energy storage applications. Bismuth oxychloride (BiOCl) is considered as one of the desirable electrode materials for its low cost, environmental benignity, and synergy with desalination technologies. Herein, we report the electrochemical activity of BiOCl in different metal ion chloride solutions of different pH. A high surface area electrode of nanosheet BiOCl on carbon cloth (n-BiOCl) is fabricated and exhibited outstanding rate capability in optimal AlCl3 electrolyte with capacities of 221 mAh g −1 at ∼1.1 A g −1 and 181 mAh g −1 at ∼4.4 A g −1 . The present work demonstrates not only the potential use of nanosheet BiOCl in a large-scale energy storage system, but also the advantages of using AlCl3 electrolyte to enhance performance of aqueous batteries.